The Role of Zakat in Empowering Islamic Economics from the Perspective of Sharia Business Management - Fatony, Achmad; Mujib, Haqibul; Al Farisi, Muhammad Salman (International Journal of Sharia Business Management, 2024)
This study aims to explore the role of zakat in empowering Islamic economics through the perspective of sharia business management. Zakat, as one of the pillars of Islam and an instrument of wealth redistribution, has great potential in improving the economic welfare of the people. This study uses a qualitative method with a case study approach on several zakat institutions and zakat beneficiaries in Indonesia. Data were collected through in-depth interviews, observations, and document analysis. The results of the study indicate that zakat not only functions as a tool to fulfill religious obligations, but also as an important strategy in empowering the community's economy. Effective implementation of zakat can increase entrepreneurial capacity, improve access to capital, and encourage local economic growth. Zakat institutions that apply the principles of sharia business management tend to be more successful in managing zakat funds and create significant positive impacts. The conclusion of this study confirms that zakat has a strategic role in empowering Islamic economics. The application of the principles of sharia business management in zakat management can increase socio-economic impacts and ensure efficient allocation. Recommendations for further research include the need for longitudinal studies to evaluate the long-term effects of zakat-based empowerment programs